Effect of Light, Medium, and Dark Roasting on Antioxidant Activity of Gununghalu Arabica Coffee (Coffea arabica L.) - Rahmawati, Irma; Purnamasari, Yeni (Rescollacom (Research Collaborations Community), 2024)
Coffee is one of the popular drinks for Indonesian people. Coffee consumption in Indonesia has increased very rapidly. The influence of lifestyle and the increasing number of cafes and coffee shops contribute to the increase in coffee consumers. One downstream processing of coffee beans is roasting coffee beans, which consists of light, medium, and dark roasting. This study aimed to determine the antioxidant activity of Gununghalu Arabica Coffee (Coffea arabica L.) with Light Roasting, Medium Roasting, and Dark Roasting Techniques. This research is an experimental study, where the antioxidant activity analysis was carried out using the DPPH method (2,2-diphenyl-1-picrylhydrazyl). Gununghalu Arabica coffee with light, medium, and dark roasting techniques positively containing flavonoids, alkaloids, saponins, tannins, and terpenoids. The results showed that the IC50 value of Gununghalu Arabica coffee for light, medium, and dark roasting was 102.94 ppm, 70.66 ppm, and 87.66 ppm. The test results show that the antioxidant activity of Gununghalu Arabica coffee with light roasting techniques are moderate, while medium and dark roasting techniques are strong. The results of this study are expected to provide implications for the development of coffee processing techniques to have maximum health benefits.